The Development of Concept Map-Based Biology Module on Animalia Invertebrate Subject Matter for 11th Grade Students - Amalina, Khilma Novia; Savitri, Dian; Safitri, Annisa (Proceeding International Conference on Science and Engineering, 2019)
The purpose of this research is to produce Concept Map-Based Biology Module and to know the quality of this module as a teaching material for 11th Grade Students. This research developed by Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. Instrument that used is checklist Questionaire. The result of Concept Map-Based Biology Module quality by a media expert, a material expert, five peer reviewer, a biology teacher is very good with presentation 86,56 %. The quality of this module is rated by fifteen 11th Grade Students of IT Abu Bakar High School too and the result is very good with presentation 83,18 %. So, Concept MapBased Biology Module on animalia invertebrate subject matter has very good quality overall and fit as a teaching material 11th Grade Students.